The psychosocial aspects of a return to sport following serious injury: A review of the literature from a self-determination perspective - Podlog, L.; Eklund, R. C. (Psychology of Sport and Exercise, 2007)
Objectives: The objective of this paper is to review the literature relevant to the psychosocial aspects of a return to sport following injury using a self-determination theoretical (SDT) framework.